Spatial identification and corridor network analysis of cultural heritage based on multi-model fusion: A case study of western Henan - Yipeng Ge; Yang Liu; Yueshan Ma; Yitong Wang; Yafei Guo; Jie He; Yalong Mao (Ecological Indicators)
Cultural heritage embodies the profound cultural connotations accumulated during the evolution of human civilization. Its protection and development are of great significance for cultural continuity, the preservation of national spirit, and sustainable development. Existing studies mostly focus on large-scale regional or isolated cultural origin points, lacking attention to medium-scale, cross-regional cultural heritage systems at the meso- and micro-levels. This study takes 761 designated cultural heritage sites in western Henan as the research objects. Using Kernel Density Estimation (KDE), Nearest Neighbor Index (NNI), Analytic Hierarchy Process (AHP), Minimum Cumulative Resistance (MCR) model, and Gravity Model (GM), this research systematically analyzes the spatial distribution characteristics and evolutionary mechanisms of cultural heritage in the region. It further constructs a hierarchical network of significant cultural heritage corridors and proposes targeted strategies for protection and development. The results indicate that the spatial distribution of cultural heritage in western Henan is characterized by non-random clustering. Overall, it presents a spatial pattern of “three cores, multiple nodes, and belt-like distribution,” with Luoyang, Dengfeng, and Gongyi as the main centers. Based on comprehensive value assessment, 41 key cultural heritage origin sites are identified. Combining spatial distribution characteristics with resistance analysis, 36 major cultural heritage corridors are delineated, including 7 primary corridors, 12 secondary corridors, and 17 tertiary corridors.